Farmers Participatory Seed Production Programme of IARI Varieties/Hybrids: A Success Story - GYANENDRA SINGH,; CHANDU SINGH,; AK SINGH,; VISWANATHAN CHINNUSAMY, (Seed Research, 2026)
Seed is a key component among all inputs for sustainable crop production. It is a vehicle for delivery of improved technologies along with utilization of inherent genetic potential of a variety /hybrid. Seed can play a critical role in achieving higher productivity, use of quality seeds alone could increase productivity by 15-20% highlights the important role of in agriculture [1, 2]. One of them of the reason for low productivity of crops is the unavailability of reliable quality seeds in the local markets. The studies indicate that the small and marginal farmers still prefer to rely on farm saved seeds and obsolete varieties. The quality seed production largely follows the limited generation’s system for seed multiplication with defined responsibility of production of different classes of seeds for different agencies. Most of the time quality seeds of new improved varieties cannot meet the demand of farmers’ as most seed producing agencies have limited land resources. This wider gap between supply and demand of quality seed can be reduced with involvement of farmers in seed production through farmers participatory seed production programme (FPSP). Considering the importance of quality seeds of crops, ICAR-Indian Agricultural Research Institute (ICAR-IARI) initiated the FPSP with a buy back system and enhance the quality seed production (Agri-horticultural crops) and revenue more than four time (2018-19 to 2023-24). The main objectives of the FPSP system is to disseminate the knowledge about new improved crop varieties/hybrids to the farmers, enhance the availability of quality seeds in the region, promote entrepreneurship development and employment generation for rural youth and women by involving them in seed production, processing and distribution of quality seeds. This system not only helps to disseminate technology but also enhances the socio-economic condition of the farming community.